ANALISA PENGARUH SUDUT NOZZLE TERHADAP EFISIENSI TURBIN PELTON SKALA LABORATORIUM - Agung Dwi Sapto; Irvan Septyan Mulyana (Jurnal Ilmiah Teknik, 2025)
Electrical energy is energy that has an important role for society. One of the benefits is for lighting. The current state of electricity in Indonesia is very concerning, especially since the oil and gas resources on earth are very limited, and one day they will run out. Therefore, various studies have been carried out to find energy sources other than oil and gas, as alternative energy sources that can be utilized according to needs. A water turbine is a device for converting the potential energy of water into mechanical energy. This mechanical energy is then converted into electrical energy by a generator. Hydropower is energy obtained from flowing water. The energy possessed by water can be utilized and used in the form of mechanical energy and electrical energy. Utilization of water energy is mostly done by using waterwheels or water turbines that take advantage of the presence of a waterfall or water flow in the river. The Pelton turbine uses a nozzle with an inner diameter of 4 mm and an angle of 60° capable of producing 0.8031 watts of power. These results were obtained at a discharge variation of 0.0002 m3/second. At the time of this test also which produces the greatest efficiency value among other tests, which is 1.231%.